‘골드원’, ‘제시골드’ 키위프루트 과실의 에틸렌 처리에 따른 과실 후숙 및 관련 유전자의 발현 - 신미희(Mi Hee Shin); 곽용범(Yong-Bum Kwack); 김윤희(Yun-Hee Kim); 김진국(Jin Gook Kim) (Weon'ye gwahag gi'sulji, 2019)
본 연구는 외생 에틸렌 처리에 따른 키위프루트 과실의 후숙 특성을 이해하고, 국내 육성 품종에 대한 적절한 수확후 관리 방법을 구명하고자 실시하였다. 국내 육성품종인 ‘골드원’과 ‘제시골드’ 두 품종을 대상으로 외생 에틸렌 0, 10, 100μL·L-1의 세가지 농도로 처리하여 과실의 품질 변화, 세포벽 분해 및 에틸렌 생합성과 관련된 유전자 발현 양상을 조사하였다. 외생 에틸렌처리에 따른 과실의 품질 변화는 두 품종 모두 외생 에틸렌 처리 과실이 무처리 과실보다 빠르게 변화하였고, 높은 처리농도에서 더욱 빠르게 변화하였지만 ‘제시골드’ 품종이 ‘골드원’ 품종과 비교하여 상대적으로 외생 에틸렌 처리에 둔감한 반응을 보였다. 과실의 유전자 발현은 ACO, ERF5, PGC, EXP2 4가지 유전자 발현이 확인되었다. 4가지 유전자 모두 ‘제시골드’보다 ‘골드원’ 품종에서 분명한 발현 차이를 보였고, 외생 에틸렌 처리농도와 처리시간에 따라 높은 발현을 보였다. We studied the effect of exogenous ethylene application on fruit ripening and its related geneexpression in kiwifruit (Actinidia chinensis) ‘Goldone’ and ‘Jecy Gold’ grown in Korea. Thefruit ripening characteristics that were affected by exogenous ethylene were evaluated toimplement the best post-harvest management practices for these two cultivars. Exogenousethylene was applied in three different concentrations, and gene expression related to cell walldegradation, ethylene biosynthesis, and fruit quality changes were examined. The kiwifruits treatedwith exogenous ethylene ripened very fast compared to non-treated kiwifruits. A. chinensis ‘Jecy Gold’was relatively insensitive to exogenous ethylene treatment when compared to A. chinensis ‘Goldone’. Exogenous ethylene accelerated ethylene biosynthesis and signaling pathways through changes in theexpression of ACO and ERF5 genes. Furthermore, PGC and EXP2 gene expression was affected byexogenous ethylene application, suggesting changes in cell wall degradation in response to ethylenesignaling. Relatively high gene expression was identified in kiwifruits treated with exogenous ethylenecompared to untreated kiwifruits. The distinct expression differences of the four genes, ACO, ERF5,PGC, and EXP2 were recorded in A. chinensis ‘Goldone’ by the concentration of exogenous ethyleneand days after treatment. KCI Citation Count: 7